Driving Supply Chain Risk Management: The Critical Roles of Supplier Trust - Mahjudin Mahjudin; Yeni Ika Pratiwi; Adi Suroso (PT. Mawadaku Sukses Solusindo, 2025)
This study examines the impact of Supplier Trust and top management involvement on enhancing Supply Chain Risk Management (SCRM), with a particular focus on the mediating role of Buyer–Supplier Relationships. The research was conducted among China manufacturing companies operating in East and Central Java, Indonesia. A quantitative approach was employed, utilizing a structured questionnaire to collect data from 44 participating firms. The collected data were analyzed using path analysis to assess both direct and indirect relationships among the variables. The results demonstrate that Supplier Trust and Top Management Involvement have significant and positive impacts on SCRM. Furthermore, both constructs significantly influence the quality of Buyer–Supplier Relationships. In turn, strong Buyer–Supplier Relationships are found to significantly improve the effectiveness of SCRM practices. These findings confirm the importance of fostering trust and leadership engagement at the strategic level, as well as nurturing relational mechanisms between buyers and suppliers to mitigate supply chain risks. The study contributes to the existing body of knowledge by empirically validating the mediating role of Buyer–Supplier Relationships in the link between internal trust and leadership factors and external risk mitigation outcomes. The practical implications suggest that manufacturing firms should invest in trust-building initiatives and engage top management in proactive supply chain risk strategies.